Beyond Food: Placing Animals in the Framework of Social Change in Post-Roman England. Issue 1 (2nd January 2018) - Holmes, Matilda
Abstract : Zooarchaeological evidence is combined with anthropological, artistic and historical sources to investigate the role of human-animal interactions during periods of social change in post-Roman England. Data from nearly 500 assemblages covering 1500 years in southern England provide a unique basis to investigate the use of non-livestock animals in diverse areas from cosmology to commodities, companions to status. Results showcase the potential for integrated studies to provide insights into the changing perceptions of animals from creatures that play a role in the afterlife, to those that are earthbound and soulless, to express status and power, to reveal a demand for spectacle and education and to reflect contrasting functions of economy alongside an increasing sentimentality for pets.